PENGARUH PEMBERIAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN DIVISI SERVICE PT. AGUNG AUTOMALL SUTOMO PEKANBARU - Maliha, Asih Lia; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Motivation is a very important activity to be done by a leader to each employee . Each motivation given an important role in supporting employee performance and can affect psychological in those employees. Motivation in the form of encouragement to excel in working , giving praise or awards , giving confidence to take responsibility , and the opportunity for the development of employee performance becomes an important indicator in the study to employees in the service division of PT . Agung Automall Sutomo Pekanbaru . The study, of 59 respondents indicated that the motivation that has been done by Head of Service Division at PT . Agung Automall Sutomo Pekanbaru .mempengaruhi keja satisfaction service division employees in the form of wage or salary level indicators , supervision , career promotion , working groups , and working conditions .. Keywords : work motivation , gratification of employment , human resources manajamen.